Economic Empowerment in Rural Java: From Unproductive Ex-Mining Site to Productive Ecological Market - Theresia Octastefani; Septian Nurmansah (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
This study aims to explore the economic empowerment activities in the Argowijil Ecological Market with the mission of environmental restoration. To get comprehensive results, this study used a qualitative method and data collection through in-depth interviews,literature review, and observation. The authors used empowerment theory by Zimmerman as an analytical tool for this research. The results showed that: first, the economic empowerment in the Argowijil Ecological Market is an accumulation results of both the empowering processes and empowered outcomes from activities at the individual, organizational, and community levels. Second, all empowerment activities to restore the ex-mining site can be realized because all stakeholders involved are willing to take a role. They work together to save the environment by transforming it into an ecological market for improving the socio-economic welfare of the community, village and the surrounding areas.